2015
DOI: 10.1002/ejhf.443
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing clinical use of biomarkers in high‐risk acute heart failure patients

Abstract: AimThe clinical value of single biomarkers at single time-points to predict outcomes in patients with acute heart failure (AHF) is limited. We performed a multimarker, multi-time-point analysis of biomarkers for the prediction of post-discharge clinical outcomes in high-risk AHF patients. Methods and resultsA set of 48 circulating biomarkers were measured in the PROTECT trial which enrolled 2033 patients with AHF. Associations between baseline levels of biomarkers and outcomes (30-day all-cause mortality, 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 29 publications
2
75
0
4
Order By: Relevance
“…Nevertheless, because IL-6 has been shown to be involved in HF development, and because levels of this inflammatory marker are increased in HF and are able to predict HF outcome in various types of HF [5,[115][116][117][118][119], it could serve as an HF biomarker. The use of IL-6 in a multi-biomarker model has been suggested [120], but circulating IL-6 levels are also affected by factors like stress, physical exercise, gender and age [119]. Moreover, circulating levels are also increased in non-HF patients; for example, elevated IL-6 plasma levels were predictive for post-operative complications in patients post-abdominal surgery [121], and IL-6 levels were associated with outcome in acute stroke patients [122].…”
Section: Inflammation Marker Il-6mentioning
confidence: 99%
“…Nevertheless, because IL-6 has been shown to be involved in HF development, and because levels of this inflammatory marker are increased in HF and are able to predict HF outcome in various types of HF [5,[115][116][117][118][119], it could serve as an HF biomarker. The use of IL-6 in a multi-biomarker model has been suggested [120], but circulating IL-6 levels are also affected by factors like stress, physical exercise, gender and age [119]. Moreover, circulating levels are also increased in non-HF patients; for example, elevated IL-6 plasma levels were predictive for post-operative complications in patients post-abdominal surgery [121], and IL-6 levels were associated with outcome in acute stroke patients [122].…”
Section: Inflammation Marker Il-6mentioning
confidence: 99%
“…Longitudinal observational studies of patients with acute or chronic heart failure also suggest correlations to serum soluble sdc1 [4547]. Neves et al studied 201 patients with acute decompensated heart failure [46].…”
Section: Introductionmentioning
confidence: 99%
“…Demissei et al also prospectively observed 2,033 patients with acute heart failure, after stabilization during hospital stay, of which 17.6% of patients died within 180 days of the study [45]. They evaluated the diagnostic accuracy of 44 biomarkers for heart failure, including sdc1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations